A retrospective analysis on maternal and neonatal outcomes in pSS/AITD pregnancies - Miaoguan Peng; Taizhen Luo; Xiaoshi Weng; Yanmei Dong; Yijuan Xie; Siqi Huang; Naifeng Liang; Shiyun Wen; Yaojie Zhai; Yingjun Xie; Yuyi Chen (Scientific Reports)
Abstract The combined impact of concurrent primary Sjögren’s syndrome (pSS) and autoimmune thyroid disease (AITD) on pregnancy outcomes remains underreported. A retrospective analysis was conducted on 115 pregnant patients diagnosed with pSS and delivering at the Third Affiliated Hospital of Guangzhou Medical University from January 2009 to July 2023. The effects of AITD on maternal and neonatal outcomes were examined and compared to a control group without AITD. In the group with pSS and AITD, the pregnancy loss rate was significantly higher than in the non-AITD group (P = 0.015), primarily reflected in the increased rate of neonatal death (P = 0.029). The proportion of term births and vaginal deliveries in the AITD group was notably reduced compared to the non-AITD group (54% vs. 81.5%; 16.0% vs. 41.5%; P = 0.001 and P = 0.003, respectively). No significant differences were observed in other maternal pregnancy outcomes, including induced abortion, spontaneous abortion, therapeutic abortion, and premature delivery (P > 0.05). The average birth weight of newborns in the pSS with AITD group was significantly lower than in the pSS without AITD group (2587.70 ± 720.50 g vs. 2812.54 ± 495.30 g, P < 0.001). Additionally, the rate of low-birth-weight infants in the pSS with AITD group was higher than in the pSS without AITD group (39.0% vs. 19.7%, P = 0.032). However, no significant differences were found between the two groups in the rates of fetal death, neonatal live birth, and fetal distress (P > 0.05). These results emphasize the importance of monitoring and managing thyroid health during pregnancy to optimize maternal and neonatal outcomes. Further exploration is essential to unravel the precise mechanisms through which AITD impacts fetal growth and to identify potential interventions to mitigate these effects.